In Silico Analysis of Secang Wood Compounds (Caesalpinia sappan L.) as Antibacterial Candidates Against Salmonella typhi Causing Typhoid Fever (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2025)
Typhoid fever is one part of a significant global health problem in the world because it causes gastrointestinal infections in humans, which encourages the search for natural remedies as an alternative option. This study examines the antibacterial potential of a widespread traditional medicinal plant in Indonesia, namely Secang Wood (Caesalpinia sappan L.). Through in silico approach, this study investigated the chemical interaction and binding affinity of the main compounds, such as Brazilin, Brazilein, Sappanchalcone, Caesalpiniaphenol, Quercetin, Sappanone A, Sappanone B, Hematoxylin, Butein with Salmonella typhi protein. Molecular docking analysis showed that Sappanone A showed high binding affinity energy of -9.2 kcal/mol, Butein and Sappanchalcone of -9.0 kcal/mol, then Quercetin and Brazilein showed binding affinity of -8.9 kcal/mol indicating significant potential as DNA gyrase inhibitors. Drug similarity analysis confirmed that Sappanone A, Butein, Sappanchalcone, Quercetin, and Brazilein have suitable characteristics to be further developed as therapeutic agents. The results of this study indicate that compounds from Secang Wood (Caesalpinia sappan L.) have the opportunity to become viable antibacterial agent candidates. Further research is needed to isolate and test the effectiveness of these compounds in preclinical and clinical studies. These findings strengthen the role of traditional Indonesian herbal medicine as a natural therapeutic approach in dealing with typhoid fever infection.